COMMERCIAL COMPETITION TO GOVERMENT MONOPOLY IN TELEVISION - R., Karthigesu (Penerbit USM, 1987)
After enjoying a virtual monopoly of broadcasting media in the country for nearly 40 years, the Malaysian government decided to allow a private commercial TV station to operate in the country in 1984. This was a bold step and an exception to the rule in the control of broadcasting in the Asian Third . World region, where broadcasting is not only made subservient to governments, but also made to serve their specific interests.